Medication reconciliation service in hospitalized patients with infectious diseases during coronavirus disease-2019 pandemic: An observational study - ENVER, CÜNEYD; ERTÜRK ŞENGEL, BUKET; SANCAR, MESUT; KORTEN, VOLKAN; OKUYAN, BETÜL (My University, 2023)
Objectives: To determine the prevalence and type of medication discrepancies and factors associated with unintentional discrepancies and identify the rate of hospital readmission and emergency service visit within 30 days after discharge among hospitalized patients with infectious diseases and receiving clinical pharmacist-led medication reconciliation during the coronavirus disease-2019 (COVID-19) pandemic. Materials and Methods: This observational study was conducted in the internal medicine and infectious diseases wards of a tertiary university hospital between July 2020 and February 2021 among hospitalized adult patients with infectious diseases. Medication reconciliation service (including patient counseling) was provided in person or by telephone. The number and type of medication discrepancies detected during the medication reconciliation services, the acceptance rate of pharmacists’ recommendation, and factors associated with having at least one unintentional medication discrepancy at admission were evaluated. At follow-up, hospital readmission and emergency service visit within 30 days after discharge were assessed by telephone. Results: Among 146 patients, 84 (57.5%) had at least one unintentional discrepancy at admission. Only three unintentional discrepancies were determined in three patients at hospital discharge. All the pharmacists’ recommendations for medication discrepancies were accepted by the physicians. Having COVID-19 [odds ratio (OR): 2.25, 95% confidence interval (CI): 1.15-4.40; p<0.05], being at a high risk for medication error (OR: 2.01, 95% CI: 1.03-3.92; p<0.05), and higher number of medications used at home (OR: 1.41, 95% CI: 1.23-1.61; p<0.001) were associated with having at least one unintentional discrepancy at admission. The rates of 30 day hospital readmission and admission to the emergency medical service were 12.3% and 15.8%, respectively. Conclusion: Medication reconciliation service provided by in-person or by telephone was useful for detecting and solving unintentional medication discrepancies during the COVID-19 pandemic.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TROPİKAL TIP; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MICROBIOLOGY; TROPICAL MEDICINE; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmasötik bilim; Molecular Medicine; Pharmaceutical Science; clinical pharmacist; COVID-19; infectious disease medicine; Medication reconciliation; unintentional discrepancy; Medication reconciliation; clinical pharmacist; infectious disease medicine; COVID-19; unintentional discrepancy